The design and efficiency of a physical education program to promote attitudinal changes towards people with visual impairments - Cordente Mesas, David; González Víllora, Sixto; Contreras Jordán, Onofre (Special Education, 2017)
The main goal of this study was to design, and confirm the efficiency of, a formative Physical Education program with the purpose of improving schoolchildren’s attitudes towards people who have a visual impairment. The participants were 910 students aged 9 to 13 years old from the region of Castilla-La Mancha (Spain). Participants simulated visual impairment during eight Physical Education sessions within the context of play and a sports-based learning environment. They completed an attitudinal questionnaire both pre and post the intervention. The author’s (2018) aim was to evaluate children’s attitudes toward both visual impairment and integrated Physical Education CAIPE-R (Block, 1995). Both a descriptive and comparative analyses, as well as ANOVA, were conducted. The results indicated a significant improvement in children’s attitudes toward those with visual impairment. Therefore, this program would be efficacious when applied in schools in the future in order to promote a better attitude toward inclusion.